Genetics Underlying an Individualized Approach to Adult Spinal Disorders - Walker, Corey T.; Bonney, Phillip A.; Martirosyan, Nikolay L.; Theodore, Nicholas (Frontiers in Surgery, 2016)
Adult spinal disorders are a significant cause of morbidity across the world and carry significant health and economic burdens. Genetic predispositions are increasingly considered for these conditions and are becoming understood. Advances in molecular technologies since the mid-1990s have made possible genetic characterizations of these diseases in many populations, and recent findings have provided insight into the underlying pathophysiologic mechanisms. These studies have made clear the genetic heterogeneity producing clinical phenotypes and suggest that individualized treatments are possible in the future. We review the genetics of cervical spondylotic myelopathy, ossification of the posterior longitudinal ligament, and adult lumbar scoliotic deformity, highlighting recent genetic discoveries and the potential for personalized future therapeutics for these patients.